Development of Problem-Based Learning Student Worksheets to Train Critical Thinking Skills of Students in Biology Education Study Program - Widia Wulandari; Siti Darwa Suryani; Irwandi Irwandi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Critical thinking ability is one of the important competencies that students must possess in biology learning. This research aims to develop Problem-Based Learning (PBL) Student Worksheets to train students' critical thinking skills in Plant Anatomy courses. This research uses the Research and Development method with a simplified 4-D model consisting of three stages: Define, Design, and Develop. The research subjects were second-semester Biology Education Study Program students at Universitas Muhammadiyah Bengkulu. Research instruments included media and material expert validation sheets, as well as student response questionnaires. Validation was conducted by one media expert and one material expert, then tested on 5 students (limited trial) and 22 students (extensive trial). Validation results showed that the student worksheets received a